Synthesis of Nano Silica Originated from Rice Husks using Sol Gel Method with Methanol as Solvent - Daniel Yonathan; Hans Kristianto; Arenst Andreas (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Indonesia is an agricultural country that largely livelihood of the population in plants that produce carbohydrates such as rice, corn. Of the amount of rice produced there abundant agricultural waste. Agricultural wastes are utilized in this study is rice husk. In the rice husks are fairly large silica content is 16-18%. The purpose of this study for the synthesis nano silica from rice husk with the formation of silica phases and stages of formation nano silica. Silica formation stage was conducted using leaching and burning. While the formation stage nano silica conducted using sol gel + HCl 1M. Results are examined is the influence of solvent and aging time on the purity and characteristics nano silica. At this stage of the formation of silica, the leaching process using citric acid and burning at a temperature of 7500C for 5 hours resulted in the structure of amorphous silica and silica purity reached 93.08%. At this stage of formation nano silica with sol gel method using a variation of methanol and aging time. Variations solvent used is 1: 9, 1:16 and 1:19. While variations of aging time used is 1,3 and 6 days. Highest purity silica obtained by the method of sol gel variation of solvent 1: 9 and 1 day aging period at 75.45%. While the smallest nano-sized silica obtained by the sol gel method variation of solvent 1: 9 and aging time of 3 days with a size between 50-1500 nm